Numerical Studies on Tension-leg Platform Wind Turbine In Malaysia - Ahmad Shukri, Muhammad Zulmarzuqi (Universiti Teknologi PETRONAS, 2017)
In this new era of advanced technologies, there are many solutions to overcome the energy problems among developed countries especially when it comes to non-renewable energy. A lot of high power and advanced country already implementing the usage of renewable energy technology such as wind turbine. Malaysia however, is still far from implementing such technology and still in its first step. Wind turbine technology has become more advanced in recent years with the shift from onshore to offshore to gain higher amount of wind energy. The offshore wind turbine began to develop from fixed platform to floating offshore platform. The floating wind turbine are considered to be the next step in the development of wind energy. The floating platform in this case can overcome the depth problem. The floating platform can ensure that the wind turbine can be placed in deeper water depth which in most countries has better average of wind velocity and more space.